Metrology, Inspection, and Process Control XXXVII 2023
DOI: 10.1117/12.2658279
|View full text |Cite
|
Sign up to set email alerts
|

AI-guided OCD metrology for single HAR sub-micron via measurement

Abstract: Global semiconductor packaging manufacturers are developing advanced process technologies with the rapid rise of heterogeneous packaging and 3D packaging. High-aspect-ratio (HAR) structures like through silicon vias (TSV) or redistribution layers (RDL) that come with the prevalence of 3D packaging technology have further significantly increased the difficulties in optical critical dimension (OCD) metrology. Due to emerging technical challenges, effective sub-micron HAR OCD solutions are highly demanded to reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Figure 1(a) shows the spectral receiving end of this architecture. Due to the structure's aperture being close to the wavelength scale, interference spectra can easily produce phase shifts beyond depth [7]. This study adopts this characteristic by capturing the 0 th -order reflected interference spectrum for CD measurements of sub-micron trench structures.…”
Section: Optical System Designmentioning
confidence: 99%
“…Figure 1(a) shows the spectral receiving end of this architecture. Due to the structure's aperture being close to the wavelength scale, interference spectra can easily produce phase shifts beyond depth [7]. This study adopts this characteristic by capturing the 0 th -order reflected interference spectrum for CD measurements of sub-micron trench structures.…”
Section: Optical System Designmentioning
confidence: 99%
“…However, the total depth of the measurement structures reaches only 3.0μm. In the case of optical CD (OCD) metrology, Yang et al ever reported the structural metrology of HAR TSV in 3D packaging application [3], but it faces huge challenges in 3D NAND HAR structure metrology because more and more disturbances would originate from the film getting thicker.…”
Section: Introductionmentioning
confidence: 99%